CHHATTISGARH EXCISE DUTY CONTRIBUTION ON ECONOMIC DEVELOPMENT: A CRITICAL STUDY - Nayak, Kamini; Kishan, Satya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper critically examines the contribution of excise duty to the economic development of Chhattisgarh, a rapidly growing state in central India. The primary purpose of the paper is to explore the extent to which excise duty has bolstered state revenue and its role in financing key infrastructure and welfare projects. Excise duty, particularly on goods like alcohol, tobacco, and petroleum, forms a significant portion of Chhattisgarh's fiscal income, making it crucial to understand its economic implications. Key aspects of excise duty in Chhattisgarh include its structure, collection mechanisms, and recent reforms aimed at enhancing efficiency. The paper assesses the relationship between excise duty revenues and broader economic indicators such as state GDP, employment rates, and infrastructure development. Findings from the study suggest that while excise duty contributes significantly to state revenue, its uneven enforcement and the rise of illegal markets present challenges to maximizing its potential. The paper concludes with recommendations for reforming excise policies, including better regulation and improved transparency, to ensure excise duty continues to contribute effectively to Chhattisgarh's long-term economic growth. By critically evaluating both strengths and weaknesses, this study provides a comprehensive view of excise duty's role in the state's fiscal health.